Modified zwolle score with delta-creatinine: enhancing the safety of early discharge after STEMI. (25th November 2020) - Bras, D; Pais, J; Carrington, M; Rocha, A.R; Picarra, B; Neves, D; Semedo, P; Aguiar, J
Abstract: Introduction: The Zwolle score (ZS) is recommended to identify low-risk patients eligible for early discharge after acute ST-segment elevation myocardial infarction (STEMI), but as only one-third of STEMIs have a low ZS, the discharge is often postponed. Creatinine variation (Δ-Cr) also provide prognostic information after STEMI. Purpose: The authors intend to study the "modified Zwolle Score" (MZS) model, which encompasses Δ-Cr as a variable that may enhance the discriminative power of the standard ZS. The outcome is 30-day mortality, time range that starts right after the ACS. Methods: This is a retrospective study with data from a national multicentre registry. We have included 3.296 patients with STEMI. Zwolle score was calculated for each patient. It is defined as shown in figure 1. Δ-Cr was defined as maximum serum creatinine minus admission serum creatinine. A Δ-Cr≥0.3 was assigned 2 points in the Modified Zwolle Score, after interpretation of odds ratio via multivariate analysis. For prediction quality assessment, we have performed ROC curve analysis with both scoring systems versus 30-day mortality. Regarding survival analysis, we have performed Kaplan-Meier curves with Log-rank analysis. We have also registered complications during hospital stay. Results: The sample mean age is 63±14, and it is composed by 76.8% of males. The majority of patients presented Killip Class I (87.3%). The STEMI was anterior in 49.7% of patients and inferior in 49.8% of patients. The mean admission time was 5 days. Intrahospital mortality was 3% and 30-day mortality was 4%. The mean ZS was 3.1±2.8 points, the mean MZS was 3±2.1 points and the mean Δ-Cr was 0.2±0.6mg/dL. The ROC curve analysis between ZS and early mortality revealed a c-statistic of 0.810 (CI 0.796–0.823), whereas the ROC curve between MZS and early mortality revealed a c-statistic of 0.853 (95% CI: 0.841–0.865). The ROC curves comparison showed superiority of the MZS c-statistic, with a difference between AUC of 0.043 (p<0.001, 95% CI: 0.024–0.063). Regarding low-risk patients, 30-day mortality was 3.3% using ZS (0–2 points) and 2.4% using modified ZS (0–2 points). Fifty patients (1.5%) died between 3rd and 10th day after ACS: original ZS low-risk criteria registered 0.09% and modified ZS low-risk criteria 0.06% fatalities. Kappa coefficient for intergroup concordance was good (0.73). Conclusion: We conclude that by adding Δ-Cr to the standard ZS, a renal function parameter that was lacking in the ZS, its predicting capacity regarding early mortality in patients admitted with STEMI was increased. Comparing both scores, low-risk patients defined by MZS registered less complications, 3–10 day mortality and 30-day mortality than low-risk patients defined by the original ZS. This fact may lead to better distinction of patients who will benefit from early discharge. Funding Acknowledgement: Type of funding source: None